A Layered Software Architecture for Quantum Computing Design Tools - Svore, Krysta M.; Aho, Alfred V.; Cross, Andrew; Chuang, Isaac; Markov, Igor L.; Svore, Krysta M. (IEEE Computer, 2006)
Compilers and computer-aided design tools are essential for fine-grained control of nanoscale quantum-mechanical systems. A proposed four-phase design flow assists with computations by transforming a quantum algorithm from a high-level language program into precisely scheduled physical actions.